Assessing the Effectiveness of Groper’s Appliance for Anterior Rehabilitation in Young Children after GA: Challenges and the Need for Improved Alternatives - M. I, Sheefaa.; R, Ramesh (Journal of Neonatal Surgery, 2025)
Background: Premature loss of primary anterior teeth due to early childhood caries (ECC) affects speech, chewing, and facial aesthetics. Groper’s appliance is commonly used for anterior rehabilitation in young children, yet concerns about discomfort, compliance, and durability highlight the need for further evaluation. Aim: To evaluate the clinical effectiveness of Groper’s appliance in children undergoing general anesthesia (GA) for dental rehabilitation, focusing on pain perception, compliance, dietary adaptation, and appliance durability. Materials and Methods: A prospective observational study was conducted with 40 children (aged 2–6 years) requiring anterior rehabilitation post-GA. Participants were divided into two groups: Group 1 received a standard Groper’s appliance, while Group 2 received a modified overdenture-type version. Pain perception (Wong-Baker Faces Pain Scale), compliance, dietary patterns, and appliance durability were assessed over six months. Data analysis included ANOVA and Chi-square tests. Results: Pain perception remained high in both groups, particularly during the initial weeks, with Group 1 reporting significantly greater discomfort. Compliance rates were lower in Group 1, with frequent appliance removal and discomfort-related resistance. Group 2 exhibited improved adaptation, reduced breakage, and better long-term acceptance. Dietary intake remained a challenge in both groups, with limited improvement in solid food consumption despite rehabilitation. Conclusion: Groper’s appliance is effective for anterior rehabilitation, but modifications such as an overdenture design enhance comfort, compliance, and durability. Further research is needed to explore alternative solutions.